Pengaruh Perawatan Rutin terhadap Efisiensi Bahan Bakar Mesin Induk KL. Sultan Hasanuddin 02 - Jamaluddin Jamaluddin; Rahmat Hidayat; Muh. Syuaib Rahman; Ratnawati Raising (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
Fuel efficiency is a critical indicator in ship operations and maritime education, particularly within the context of sustainability. This study addresses the issue of increasing fuel consumption and exhaust gas emissions caused by suboptimal engine maintenance practices. The objective of this research is to analyze the impact of routine maintenance on the fuel efficiency of the main engine aboard the training vessel KL. Sultan Hasanuddin 02. A quasi-experimental method was employed, involving field observations, technical measurements using a flowmeter and gas analyzer, and interviews with the Chief Engineer. Data were collected before and after the implementation of maintenance procedures based on the Planning Maintenance System (PMS). The results showed a 12.5% improvement in fuel efficiency, along with reductions in CO₂ emissions by 16.4%, NOx by 19.2%, and SOx by 18.8%. These findings demonstrate that routine maintenance not only enhances energy efficiency but also mitigates the environmental impact of the ship's propulsion system. Key supporting factors include technician competence, operational conditions of the vessel, and the quality of fuel used. This research provides both practical and academic contributions to the development of data-driven main engine maintenance guidelines, which are relevant to vocational maritime education and efforts to improve energy efficiency in the shipping sector.